Investigation of the effects of phthalates on in vitro thyroid models with RNA-Seq and ATAC-Seq - Nazzari, Marta; Romitti, Mírian; Hauser, Duncan; Carvalho, Daniel J.; Giselbrecht, Stefan; Moroni, Lorenzo; Costagliola, Sabine; Caiment, Florian (Frontiers in Endocrinology, 2023)
Abstract Phthalates are a class of endocrine disrupting chemicals (EDCs) which have been shown to negatively correlate with thyroid hormone (TH) serum levels in human and to cause a state of hyperactivity in the thyroid. However. their mechanism of action is not well described at the molecular level. We analyzed the response of mouse thyroid organoids to the exposure to a biologically relevant dose range of the phthalates DEHP, DIDP, DINP and DnOP for 24 hours and simultaneously analyzed mRNA and miRNA expression via RNA-Sequencing. Dose-series analysis showed how the expression of several genes increased or decreased at the highest dose tested. As expected with the low dosing scheme, the compounds induced a modest response on the transcriptome, as we identified changes in only mmu-miR-143-3p after DINP treatment and very few differentially expressed genes. No effect was observed on thyroid markers. Ing5 was consistently upregulated in three out of four conditions compared to control, and we observed a partial overlap among the genes differentially expressed by the treatments. Gene set enrichment analysis (GSEA) showed an enrichment in the treatment samples of the fatty acid metabolism pathway and in the control of pathways related to the receptor signaling and extracellular matrix (ECM) organization. As ING5 is a component of histones H3 and H4 acetylation complexes, we exposed the human thyroid follicular epithelial cell line Nthy-ori 3-1 to DEHP or DINP 1 μM for 5 days and analyzed changes in chromatin accessibility via ATAC-Seq. While we observed a general increase of accessibility compared to the control, we did not identify significant changes in accessibility in the identified regions. Lastly, we showed that despite having only a few differently expressed genes, different analysis methods could be applied to retrieve relevant information on phthalates, showing the potential of in vitro thyroid relevant systems analysis EDCs.